Affine-Type Model of Variable Renewable Energy and Its Application in the Uncertain Power Flow. (October 2020) - Huang, Gengye; Shao, Zhenguo; Zhang, Yan
Abstract: The intermittent variable renewable energy (VRE) results in uncertainty in distribution networks, and the existing affine iterative algorithm cannot consider the characteristics of VRE. To deal with such issues, an affine-type model of VRE considering its regulation characteristics was proposed in this paper. Furthermore, an alternating iterative algorithm based on Newton-Raphson iterative algorithm was proposed, which can consider both power flow equations and the VRE models. Finally, the effectiveness of the affine-type model of VRE and the affine iterative algorithm were evaluated on the modified IEEE 33-bus system and PG&E 69-bus system. The simulation results showed that the proposed method has sufficient completeness and slight conservativeness. Moreover, the proposed method with VRE models is superior over Monte Carlo method, particularly in terms of calculation burden.